Respuestas

¡La mejor respuesta!
2012-07-19T21:53:02+02:00

1.. 

x² +6x-16=0

x²+6x=16

x²+6x+(3)²=16+(3)²

x²+6x+9=16+9

x²+6x+9=25

   (x+3)²=25

     x+3 =√25

( Sabemos que: √25 = 5 ó -5 )

    x+3 = 5       x+3= -5

    x=5-3          x= -5-3

    x=2             x= -8

 

.: x1=2      ^     x2= -8



2..  

x² -8x-20=0

x² -8x= 20

x² -8x+(4)²=20+(4)²

x² -8x+16=20+16

x² -8x+16=36

      (x-4)²=36

         x-4=√36

(Sabemos que √36= 6 ó -6)

    x- 4=6         x- 4= -6

    x=6+4         x= -6+4

    x=10           x= -2


.: x1=10     ^    x2= -2


3..  

x² +10x+24=0

x² +10x= -24

x² +10x+(5)²= -24+(5)²

x² +10x+25 = -24+25

x² +10x+25 = 1

        (x+5)² = 1

           x+5 = √1

(Sabemos que √1 = 1 ó -1)

    x+5 =1         x+5= -1

    x=1 -5          x= -1-5

    x= -4            x= -6

 

.: x1= -4     ^    x2= -6


*Espero haberte ayudado, saludos.